Silicon carbide particulates incorporated into microalloyed steel surface using TIG: microstructure and properties. Issue 1 (2nd January 2020) - Muñoz-Escalona, P.; Sillars, F.; Marrocco, T.; Edgar, R.; Mridha, S.; Baker, T. N.
ABSTRACT: Surface metal matrix composites have been developed to enhance properties such as erosion, wear and corrosion of alloys. In this study, ∼5 µm or ∼75 SiC particulates were preplaced on a microalloyed steel. Single track surface zones were melted by a tungsten inert gas torch, and the effect of two heat inputs, 420 and 840 J mm −1, compared. The results showed that the samples melted using 420 J mm −1 were crack-free. Pin-on-disk wear testing under dry sliding conditions was conducted. The effects of load and sliding velocity were used to characterise the performance of the crack-free samples. Microstructural and X-ray diffraction studies of the surface showed that the SiC had dissolved, and that martensite, was the main phase influencing the hardness.